Menander in contexts - Sommerstein, Alan H. (Routledge monographs in classical studies, 2014)
Context: society (gender, slavery, war) -- Money and love in Menandrian comedy / Horst-Dieter Blume -- Menander and the Pallake / Alan H. Sommerstein -- Rethinking rape in Menander's comedy and Athenian life: modern comparative evidence / Sharon L. James -- Relationships among slaves in Menander / Eftychia Bathrellou -- Military culture and Menander / Mario Lamagna -- Context: dramatic tradition -- Staging and constructing the divine in Menander / Sarah Miles -- The unity of time in Menander / Robert Germany -- Aspects of recognition in Perikeiromene and other plays / William D. Furley -- Failing communication in Menander and others / Gunther Martin -- Context: philosophy and medical thought -- Menander and the peripatos: new insights into an old question / Angelo Casanova -- Menander, Aristotle, chance and accidental ignorance / Valeria Cinaglia -- Melancholic lovers in Menander / Christophe Cusset -- Context: posterity -- On the reception of Menander in the imperial period / Orestes Karavast and Jean-Luc Vix -- "Not even Menander would use this word!": perceptions of Menander's language in Greek lexicography / Olga Tribulato -- An ideal reception: Oscar Wilde, Menander's comedy, and the context of Victorian classical studies / Serena Witzke -- Menander's Epitrepontes in modern Greek theatre: the poetics of its reception and performance / Stavroula Kiritsi
based on the international conference with the same title held at Lincoln Hall in the Univeristy of Nottingham, 23 - 25 July 2012
Keywords: Menander -- of Athens -- Criticism and interpretation; Aufsatzsammlung; Konferenzschrift; Menander